S-alkylbenzothiophenium-based solid-state electrolyte for efficient quantum-dot sensitized solar cells. (December 2019) - Wang, Yefeng; Zeng, Jing Hui; Zhao, Guangtao
Highlights: In this work, the benzothiophene structure was introduced into the organic ionic crystals (OICs) for the cost-effective small molecule organic hole transport materials. The synthesized OIC, S -methyl benzthiophenium tetrafluoroborate ([MBT]BF4 ), not only exhibits the high ionic conductivity, but also shows the good interface compatibility with the photoanode. Applying [MBT]BF4 into quantum-dot sensitized solar cell (QDSSC) as the matrix of solid-state electrolyte, the device achieves a power conversion efficiency of 5.49% which is higher than those previously reported for the solid-state QDSSCs. Abstract: Developing cost-effective solid-state electrolyte is a urgent issue and a common request for (photo) electrochemical cells. In this work, a series of organic ionic conductors based on the S -substituted benzothiophenium salts have been synthesized via a simple and low-cost method. Research on the thermal behavior, optical absorption and ionic conductivity shows that S -methylbenzothiophenium tetrafluoroborate ([MBT]BF4 ) among them have the good thermal stability, high ionic conductivity and no absorption in the visible region. And the solid-state electrolyte using [MBT]BF4 as the matrix exhibits the good interfacial compatibility with photoanode. Applying this solid-state electrolyte into the quantum-dot sensitized solar cell (QDSSCs), the device achieves an open circuit voltage of 0.71 V, a short circuit current density of 20.73 mW cm −2, and a power conversion efficiency of 5.49% which is higher than those previously reported for the solid-state QDSSCs.